Gugatan Citizen Lawsuit Dalam Sistem Hukum Di Indonesia - Solissa, Ferdinan Rifaldi; Salmon, Hendrik; Lakburlawal, Mahrita Aprilya (PATTIMURA Law Study Review, 2024)
ABSTRACT: A citizen lawsuit is a lawsuit mechanism known in the common law legal system, in which citizens file a lawsuit against the state in the name of the public interest to sue the state for acts of opposition or violation committed by the state for failing to fulfill its legal obligations. The purpose of a citizen lawsuit is to protect citizens from the possibility of losses experienced by citizens, based on negligence or negligence on the part of the state. In the Indonesian legal system itself, citizen lawsuits have not been clearly regulated in Indonesian law, be it Supreme Court regulations or other laws and regulations in Indonesia. So far, citizen lawsuit cases in Indonesia have been used by judges using articles 5 and 10 of the Law. Law 48 of 2009 concerning Judicial Power The problems raised by the author are: What is the position of citizen lawsuits in the legal system in Indonesia, m. The research method used is normative juridical, the research type is descriptive analytical, the legal materials used are primary, secondary and tertiary. The technique for collecting legal materials uses library research and is then analyzed using qualitative methods. The research results show that the position of citizen lawsuits in the Indonesian legal system refers to previous judge's decisions which have become jurisprudence.